The Role of Add-On Lacosamide Therapy in the Treatment of Focal Onset Epilepsy - Koc, Guray; Bek, Semai; Karadas, Omer; Eroglu, Erdal; Gokcil, Zeki (Kare Publ, 2017)
Objectives: The aim of this study was to retrospectively evaluate the efficacy and safety of lacosamide (200-300-400 mg/day) as adjunct treatment in patients with uncontrolled focal-onset seizures taking 2 or more antiepileptic drugs (AED). Methods: A retrospective review of the medical records of patients with uncontrolled focal epilepsy who received lacosamide as add-on therapy for at least 6 months was performed. Data collected and analyzed included demographic information, lacosamide dosing, concomitant AED therapy, and seizure activity in first and sixth months. Results: A total of 83 patients were evaluated. The mean percent reduction in seizure frequency per month was 38.98% in the first month and 33.22% in the sixth month. In all, 53% of the patients had a decrease in seizures of 50% or more in the first month, and 47% saw a similar decrease in the sixth month. The percentage of those taking a sodium channel blocking AED in addition to lacosamide was 97.6%. Doserelated adverse events reported included dizziness, nausea, diplopia, gastroenterological side effects, headache, itchy skin, and blurred vision. It was determined that all of the patients with drug-related side effects were taking a sodium channel blocking AED concomitantly with lacosamide. Conclusion: Adjuvant treatment with lacosamide reduced seizure frequency for patients with uncontrolled focal-onset seizures.
Keywords: Efficiency; focal epilepsy; lacosamide